Forum : Internationale Kunstmesse Zürich. (Zürich : Forum Internationale Kunstmesse, 1984)
Winters, Robin ; Hien, Albert ; Turin, Bernard ; Oberhuber, Oswald ; Egerer, Evelyne ; Richter, Gerhard ; Hutchinson, Peter ; Buraglio, Pierre ; Spoldi, Aldo ; Strau, Josef ; Garouste, Gérard ; Szczensy, Stefan ; Quik ; Merlino, Silvio ; Luyten, Mark ; Fleury, Jean-Dominique ; Anzinger, Siegfried ; van Elk, Ger ; Calzolari, Pierpaolo ; Kunc, Milan ; Merz, Mario ; Duchateau, Hugo ; Iseli, Rolf ; Parent, Claude ; Attersee, Christian Ludwig ; Basquiat, Jean-Michel ; Kalff, Jan ; Baechler, Donald ; Lack, Stephen ; Seldon, Roger ; Gross, Rainer ; Glantzman, Judy ; Billgren, Ola ; Fetting, Rainer ; Connelly, Chuck ; Disler, Martin ; Meyer, Jürgen ; Phillips, Jay ; Suvero, Mark di ; Paschke, Ed ; Buren, Jodi ; Tirelli, Marco ; Bates, David ; Crowley, Graham ; Dennis, Donna ; Alberola, Jean-Michel ; Pistoletto, Michelangelo ; Augeri, Guy ; Raynaud, Jean Pierre ; Haring, Keith ; Bruna-Hautman, Sigefride ; van den Broeck, Frank ; Kluge, Gustav ; Chevalier, Peter ; Schulze, Andreas ; Kocherscheidt, Kurt ; Bonami, Francesco ; Wachweger, Thomas ; Oroschakoff, Haralampi ; Brandl, Herbert
Duits & Engels & Frans & Italiaans
Forum Internationale Kunstmesse Zürich 1984, Forum, 22. - 27. November 1984, Züspa Hallen, Zürich
kunstcatalogus